Tunable Optical Filter Based on Thin Film Lithium Niobate Photonic Crystals - Luyao Wang; Tianyu Yang; Haolei Feng; Shengya Zhang; Jianguo Liu; Zeping Zhao (Photonics)
In this paper, we propose a tunable optical filter with a high Q factor based on photonic crystal technology, achieving a Q factor of 442.85 using thin film lithium niobate technology. By proportionally adjusting the dimensions of the unit structure, this filter enables coarse tuning across the 1520–1570 nm range (C band). Furthermore, by utilizing the thermo-optic effect of lithium niobate, we can achieve fine-tuning of the optical filter within a temperature range of 300 K to 600 K, allowing for a center wavelength tuning capability of up to 3.7 nm. This design not only enhances the filter’s performance but also broadens its potential applications in optical communication and optical signal processing.